Зовнішня торгівля товарами України з Польщею, Румунією, Словаччиною та Молдовою: аналіз і прогнозування - Тоцька, Олеся Леонтіївна (Волинський національний університет імені Лесі Українки, 2022)
Метою статті є комплексний аналіз і прогнозування експортно-імпортних операцій з товарами між Україною та сусідніми країнами: Польщею, Румунією, Словаччиною і Республікою Молдова. Аналіз проводився на основі статистичних даних Державної служби статистики України за 2011–2021 рр. Для прогнозування показників зовнішньої торгівлі товарами України на три роки (2022–2024) використано метод екстраполяції трендів. Визначено, що найбільше товарів експортувалось до Польщі (від 3,8 до 7,7 %), найбільші частки в імпорті товарів належали також Польщі (від 3,9 до 7,6 %). Згідно прогнозних моделей, передбачається зростання експортно-імпортних операцій України з усіма аналізованими країнами. Найбільшу імовірність мають прогнозні показники експорту товарів до Польщі та Румунії.

Poland, Romania, Slovakia and the Republic of Moldova are Ukraine’s geographical neighbors. The proximity of the location facilitates Ukraine’s foreign trade with these countries. However, export-import operations with each neighboring country have their own characteristics and prospects. The purpose of the article is a comprehensive analysis and forecasting of export-import transactions with goods between Ukraine and neighboring countries: Poland, Romania, Slovakia and the Republic of Moldova. Results. The analysis was conducted on the basis of statistical data of the State Statistics Service of Ukraine for 2011–2021. The method of extrapolation of trends was used to forecast the indicators of foreign trade in goods of Ukraine for three years (2022–2024). Exports of goods from Ukraine to Poland were quite high: from 1,977.3 million dollars US in 2015 to 5,227.6 million dollars US in 2021; imports – from 2,324.0 million dollars US in 2015 to 4,958.8 million dollars US in 2021. Exports of goods from Ukraine to Romania were low: from 546.9 million dollars US in 2013 to 1,543.7 million dollars US in 2021; imports – from 318.2 million dollars US in 2015 to 1,117.2 million dollars US in 2011 Exports of goods from Ukraine to Slovakia were low: from 446.8 million dollars US in 2020 to 999.4 million dollars US in 2021; imports – from 346.3 million dollars US in 2015 to 1,143.4 million dollars US in 2020. Exports of goods from Ukraine to the Republic of Moldova were low: from 481.1 million dollars US in 2016 to 895.7 million dollars US in 2013; imports are even lower – from 41.2 million dollars US in 2015 to 125.9 million dollars USA in 2011. Conclusions. Among the analyzed countries, most goods were exported to Poland (from 3.8 to 7.7 %). The largest shares in imports of goods also belonged to Poland (from 3.9 to 7.6 %). According to the forecast models, the growth of export-import commodity operations of Ukraine with all analyzed countries is expected. However, the war on the territory of Ukraine may hinder their implementation. Forecasts of exports of goods to Poland and Romania are the most likely.
Keywords: експорт; імпорт; товари; Україна; Польща; Румунія; Словаччина; Республіка Молдова; export; import; goods; Ukraine; Poland; Romania; Slovakia; the Republic of Moldova; 339.5-047.44/.72(477:438:498:437:478)